Dual axis solar tracking system / Hafizuddin Ahmad Sharipudin - Ahmad Sharipudin, Hafizuddin (2015)
Increased demand for energy causes a fossil fuel source available is decreased. Environmental pollution that occurred raise concerns. This problem causes people to exploit new technologies to produce clean and renewable energy such as solar energy. In this technical paper, a system for collecting the solar energy from the sun was created by using solar tracking system. The system used PIC microcontroller in order to control the movement of solar panel towards the sun. Theoretically described as the energy collected from the sun will be better if the solar panel position always facing the sun.